2008
DOI: 10.1007/s00432-008-0500-5
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evaluation of intravesical paclitaxel and combined bcl-xL antisense oligodeoxynucleotide treatment for orthotopic urothelial carcinoma

Abstract: We present an in vivo evaluation of intravesical treatment with paclitaxel and combined bcl-xL AS-ODNs. Despite efficient tumor size reduction, no gain was observed when adding bcl-xL AS-ODNs in this experimental setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Furthermore, the inhibitory efficiency of AS-ODNs depended on the sequences and modifications of the constructs as well as on the type of delivery agent (11). However, it was reported in several studies that a treatment of BCa cells with Bcl-xLdirected AS-ODNs alone did not induce significant inhibition of viability, whereas a combination with chemotherapeutics promoted a significant increase of apoptosis in tumor cell lines as evidence for chemosensitization (11,14,17). To improve the efficiency of Bcl-xL-targeted AS-ODNs we systematically designed and characterized new AS-ODNs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the inhibitory efficiency of AS-ODNs depended on the sequences and modifications of the constructs as well as on the type of delivery agent (11). However, it was reported in several studies that a treatment of BCa cells with Bcl-xLdirected AS-ODNs alone did not induce significant inhibition of viability, whereas a combination with chemotherapeutics promoted a significant increase of apoptosis in tumor cell lines as evidence for chemosensitization (11,14,17). To improve the efficiency of Bcl-xL-targeted AS-ODNs we systematically designed and characterized new AS-ODNs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the described Bcl-xL-directed AS-ODNs alone did not promote a significant inhibition of viability of BCa cells (11,17,18). For this reason, alternative AS-ODNs with a potentially higher inhibitory efficiency would be preferable.…”
Section: Introductionmentioning
confidence: 95%
“…Moreover, Bcl-xL not only inhibits cell apoptosis and boosts survival of cells, but also resists apoptosis mediated by cancer suppressor genes such as P53 and C-myc (16). Research has shown that the Bcl-xL gene was highly expressed in many types of tumor cells (17,18), and that Bcl-xL, which plays a role in the occurrence and development of bladder cancer, may be used for the prognosis and treatment of the relapse of bladder cancer (19,20).…”
Section: Discussionmentioning
confidence: 99%
“…Although Bcl-2 was not overexpressed frequently in UC of urinary bladder (Kirsh et al , 1998), Bcl-xL is expressed at a high frequency (Lebedeva et al , 2001; Korkolopoulou et al , 2002), therefore, it might become the target of treatment in UC. Several studies have evaluated the prognostic role of Bcl-xL protein expression in bladder carcinoma, especially for superficial bladder carcinoma (Gabriel et al , 2008; Bolenz et al , 2009). However, the status of Bcl-xL expression in UTUC tissues and its prognostic significance are unclear.…”
mentioning
confidence: 99%